Temporal Trends and Early Outcomes of Transcatheter versus Surgical Mitral Valve Repair in Atrial Fibrillation Patients - Chi Zhou; Kai Tan; Weili Liu; Shaohua Li; Zongyi Xia; Yanxu Song; Zhexun Lian (Journal of Interventional Cardiology)
Objectives. To study trends of utilization, in-hospital outcomes, and short outcomes in patients undergoing transcatheter mitral valve repair (TMVR) vs. surgical mitral valve repair (SMVR) in atrial fibrillation (AF). Background. TMVR is a treatment option in inoperable or high-risk patients with mitral regurgitation (MR). AF is a common comorbidity of MR. Data comparing between TMVR and SMVR in MR patients with AF is lacking. Methods. The National Readmission Database from 2016 to 2019 was utilized to identify hospitalizations undergoing TMVR or SMVR with AF. Outcomes of interest included mortality, postoperative complications, length of stay, and 30-day readmission rate. Results. A total of 9,195 patients underwent TMVR and 16,972 patients underwent SMVR with AF; the number of AF undergoing TMVR was increasing from 1,342 in 2016 to 4,215 in 2019 and SMVR. The incidence of in-hospital mortality decreased from 2.6% in 2016 to 1.8% in 2019. We identified length of stay>5 days, dyslipidemia, cerebrovascular disease, heart failure with reduced ejection fraction, and urgent/emergent admissions as independent risk factors for in-hospital mortality. After matching, we included 4,680 patients in each group; the in-hospital death, transfusion, acute kidney injury, sepsis, stroke, and mechanical ventilation were lower in TMVR compared with SMVR. TMVR was associated with a similar rate of all-cause readmission at 30 days compared with SMVR. Conclusion. Patients with AF receiving TMVR have been increasing along with progressive improvement in in-hospital death and length of stay. Compared to SMVR, AF patients receiving TMVR had a lower rate of in-hospital death and postoperative complications.